Association between conditioning capacities and shooting performance in professional basketball players: an analysis of stationary and dynamic shooting skills - Pojskic, H.; Sisic, N.; Separovic, V.; Sekulic, D. (The Journal of Strength and Conditioning Research, 2018)
Little is known about the influence of conditioning capacities on shooting performance in basketball. The aim of this study was to examine the relationship between different conditioning capacities and shooting performance in professional basketball players. In this investigation, we examined 38 males (all perimeter players; height: 185.5 ± 6.73 cm; mass: 78.66 ± 10.35 kg). Conditioning capacities were evaluated by tests of muscular strength, aerobic endurance, jumping and throwing capacities, sprinting speed, preplanned agility, anaerobic endurance, and fatigue resistance. Shooting performance was evaluated using game statistics, as well as 6 tests of shooting performance performed in controlled settings: (a) 3 tests of static (i.e., nonfatigued) shooting performance (standardized execution of 1- [S1], 2- [S2] and 3-point shots [S3] in stationary conditions), and (b) 3 tests of dynamic (i.e., fatigued) shooting performance (standardized execution of 1- [D1], 2- (D2), and 3-point shots [D3] in dynamic conditions). All 3 dynamic shooting tests and the S1 test were significantly (p = 0.05) correlated with corresponding game statistics. Multiple regression indicated that conditioning capacities were significantly related to D1 (R 2 = 0.36; p = 0.03), D2 (R 2 = 0.44; p = 0.03), S3 (R 2 = 0.41; p = 0.02), and D3 (R 2 = 0.39; p = 0.03) tests. Players with a higher fatigue resistance achieved better results on the D1 test (ß = -0.37, p = 0.03). Preplanned agility (ß = -0.33, p = 0.04), countermovement jump (ß = 0.42, p = 0.03), and fatigue resistance (ß = -0.37, p = 0.02) were significant predictors of D2 performance. The countermovement jump (ß = 0.39, p = 0.04), medicine ball toss (ß = 0.34, p = 0.04), and anaerobic endurance (ß = 0.46, p = 0.04) predicted the results of D3 performance. Jumping, throwing, and anaerobic endurance capacities were good determinants of the skill of dynamic shooting over a long distance. These findings emphasize the importance of explosive power and anaerobic capacity as determinants of shooting performance in high-level basketball players.